Zrozumieć totalitaryzm - Siwek, Anna (Pamięć i Sprawiedliwość, 2013)
Can Józef Tischner’s reflection on totalitarianism prove helpful in understanding the events which took place in our country in the second half of the 20 th century? Does the author, who sees totalitarianism as a specific way of thinking affecting the shape of human relationships, reveal part of the truth about the experiences of the Polish society? By providing positive answers to the above questions, the article presents Tischner’s analytical viewpoint – in order to understand totalitarianism we need to go beyond its conventional meaning, in the categories of a political system, towards an ethical perspective. According to Tischner, totalitarianism is basically the experience of evil. Evil causes the deformation of human mentality, as people overwhelmed with fear and the desire to survive are guided with the principle of retaliation towards other people. The main source of evil is politics in its communist form, which generates a political way of thinking and negatively transforms the sphere of human relations. A lack of faith in the possibility to do well is the trademark of people shaped by totalitarian experiences. Are changes inflicted in this way deep and irrevocable? On the one hand, the reflection of the philosopher from Cracow concerning the origins of the Independent Selfgoverning Trade Union “Solidarity” (NZZ „Solidarność”) shows that the plan to completely destroy the ethical dimension of human relationships, expressed in the words of the Gospel “Carry one another’s burdens; in this way you will fulfill the law of Christ”, did not succeed. On the other hand, by presenting totalitarianism not only as a political system, Tischner provokes us to self-reflect on our condition “here and now” and search for an answer to the question: how many totalitarian traces do we still have, which despite the fall of the communist system continue to affect our actions and attitudes towards other people.